Change agency in occupational context: lessons for HRM. (January 2014) - Wylie, Nick; Sturdy, Andrew; Wright, Christopher
<x xml:space="preserve">Abstract</x> Change agency is seen as a key route to reducing the occupational vulnerability of human resource management (HRM). However, few look outside of the HRM context to consider change agency more broadly in organisations. Drawing on a study of change agency units in British organisations, we argue that challenges to occupational credibility and competing jurisdictional claims have wider implications for the role of HR practitioners. In particular, change agency is better seen as replaying rather than resolving the ambiguity of HRM's role and identity in organisations.